Developing a gum arabic - citric acid bioadhesive for liquid bandage application - Ayapana, Chielo Marie N.
Open wounds resulting from either a surgical or a traumatic disruption of tissues layers should be sufficiently covered to prevent infection and promote fast wound healing. At present, the application of bioadhesives as liquid bandages is being considered as alternative to conventional wound dressings such as dry gauzes due to several advantages. However, commercially available liquid bandages are relatively expensive.Thus, there is a need to develop a novel bioadhesive that can be produced at a lower cost. In this study, a novel bioadhesive was synthesized by mixing different ratios of gum arabic (Gum) to citric acid (CA). Analysis revealed that 3:2 Gum-to-CA was the best composition among all tested ratios with a surface hydrophilicity that was reportedly favorable for optimal wound healing. Antimicrobial assay showed that Gum-CA did not show antifungal activity against C. albicans but effectively inhibited E. coli, S. aureus, P. aeruginosa, and S. marcescens. Cytotoxicity test proved satisfactory, with cell viability >70% as required by ISO 10993-5:2009. Water uptake was measured at 544.69% for 4:1 Gum-CA ratio and 300.31% for 3:2 Gum-CA ratio, which suggested ability to absorb exudation and provide a moist environment. The T-peel test showed that adhesion strength of a 2:3 Gum-CA sample is comparable with that of commercialized liquid bandage. Lastly, the calculated total material cost of Gum-CA was significantly lower than that of the liquid bandages currently available in the market, hence indicating that this bioadhesive can be produced and sold commercially at a significantly lower price.